2017
DOI: 10.1016/j.neuron.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the Default Activity Pattern of the Cortical Network

Abstract: Slow oscillations have been suggested as the default emergent activity of the cortical network. This is a low complexity state that integrates neuronal, synaptic, and connectivity properties of the cortex. Shaped by variations of physiological parameters, slow oscillations provide information about the underlying healthy or pathological network. We review how this default activity is shaped, how it acts as a powerful attractor, and how getting out of it is necessary for the brain to recover the levels of compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
142
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(153 citation statements)
references
References 81 publications
8
142
0
3
Order By: Relevance
“…Slow wave state has been proposed to constitute the default activity pattern of the cortex 21 ; This bimodal activity pattern -periods of quiescence interrupted by short bursts of activity -generates waves that can propagate across the cortex 24,59 . We recently showed that these waves generate a cortex-wide increase in BOLD activity 11 which may be responsible for the cortex-wide increase in functional connectivity in slow wave state.…”
Section: Population Down-up Transitions Drive Functional Connectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Slow wave state has been proposed to constitute the default activity pattern of the cortex 21 ; This bimodal activity pattern -periods of quiescence interrupted by short bursts of activity -generates waves that can propagate across the cortex 24,59 . We recently showed that these waves generate a cortex-wide increase in BOLD activity 11 which may be responsible for the cortex-wide increase in functional connectivity in slow wave state.…”
Section: Population Down-up Transitions Drive Functional Connectivitymentioning
confidence: 99%
“…In persistent state, which can occur during but is not limited to awake periods, neurons are rather depolarized, sparsely active, leading to temporally dynamic, modality specific, network configurations 18 . In contrast to the persistent state, stands the bimodal activity pattern of slow oscillations, or slow wave state which has been extensively described 5,11,[19][20][21][22][23][24][25] , but only most recently in the framework of BOLD fMRI 11,26,27 . The corresponding low-frequency component ranges at 0.2-1 Hz, reflecting alternating activity patterns: active ("up") periods in which cells are depolarized and fire action potentials in temporally restricted periods, and silence ("down") periods with rather hyperpolarized membrane potentials and an almost complete absence of neuronal activity 28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low frequency fluctuations of the blood-oxygenation level-dependent fMRI signal putatively arise from the spontaneous neural activity of microcircuits and reflect the functional integrity of the brain (Sanchez-Vives, Massimini, & Mattia, 2017). These fluctuations are sensitive to changes in brain development (Smyser et al, 2013;Wu et al, 2016), aging (Biswal et al, 2010), cognitive deficits (Z.…”
mentioning
confidence: 99%
“…Slow waves have been hypothesized to represent the default mode of cortical network activity (Sanchez‐Vives, Massimini, & Mattia, ). During UP states, there is synchronization in beta and gamma frequencies, synaptic gain modulation, modulation of replay and memory formation, and some cortical features might inform about transitions between unconsciousness and consciousness [reviewed in Sanchez‐Vives et al, ]. An intriguing paradox exists in that astrocytes induce a synchronized state, but also mediate cholinergic and noradrenergic neuromodulations, which are characteristically associated with asynchronous, high‐rate activity that facilitates sensory processing (Lee & Dan, ).…”
Section: Computational Lessons Learned From Systems‐like Studies In Amentioning
confidence: 99%